The Innovation-Technological Provision for Modernization of the Priority Branches of Industry of Ukraine - Khaustova Viktoriia Ye.; Kramarev Hennadii V.; Zinchenko Volodymyr A. (Bìznes Inform, 2019)
The article is concerned with substantiating the innovation-technological provision for modernization of the priority branches of industry of Ukraine. It is defined that technological progress is one of the main factors of long-term growth. It is proved that one of its basic factors is the stable functioning of the industrial complex. It is defined that tendencies of development and structural changes of industrial complex of Ukraine do not correspond to those which are formed in the leading world countries that necessitates substantiation of directions of modernization of the priority branches of the country’s industry and the innovation-technological provision for these processes. It is identified that different definitions are used to characterize conceptions of the technologically innovative development, among which the «Industry 4.0» appears one of the most reasonable. Interpretations of the concept of «Industry 4.0» in the scientific literature and practice are analyzed, it is suggested to interpret it as the development and merging of automated production, data exchange and production technologies into a single self-regulating system, with or even without the minimal human intervention in the production process. The elaborations, constituting the basis of the conception of «Industry 4.0» together with components of its foundation are considered. It is proposed to allocate the following principles of the conception of «Industry 4.0»: digitalization, customization, intellectualization, automation, cyber-physicalization, miniaturization. It is defined that each of the principles is implemented through certain technologies; the information technology platform of the conception of «Industry 4.0» is formed, the basis of which are two integration systems: cyber-physical system and the industrial Internet of things. The distinguishing features of the traditional industrial enterprise and production within the framework of the conception of «Industry 4.0» are considered.